Development of a Tool for the Assessment of Nurses' Attitudes Toward Delirium - Papastavrou, Evridiki; Papaioannou, Maria; Evripidou, Melina; Tsangari, Haritini; Kouta, Christiana; Merkouris, Anastasios (My University, 2019)
Background and Purpose: The prevalence of delirium during hospitalization is high in older patients and there is evidence of staff regarding them as unpopular or a burden. This study aims to develop an instrument examining nurses' attitudes toward patients with delirium. Methods: Stages included (a) content identification, (b) content development, (c) content critique, (e) pilot study with a test–retest reliability, (f) field study consisting of psychometric testing of the internal consistency and construct validity. Results: The Cronbach's alpha was 0.89 and the stability reliability was acceptable. The factor analysis resulted in three factors explaining a total of 56.5% of the variance. hese factors are “beliefs,” “behavior,” and “emotions,” explaining 37.025%, 12.792%, and 5.652% of variance. Conclusions: The Attitude Tool of Delirium (ATOD) is a reliable and valid instrument for the assessment of attitudes toward delirium.
Keywords: Attitude; Delirium; Nursing; Validation